The end of negotiable instruments bringing payments systems law out of the past - Rogers, James Steven, 1951- (New York : Oxford University Press, 2012)
James Rogers challenges the basic assumptions of the law of checks and notes and its history, and provides a well-reasoned account of how the law could be changed to better suit the evolution of new payment technologies.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Negotiable instruments -- United States